Evaluating the physicochemical properties and efficacy of recently expired and aged antivenom products from Thailand and Taiwan. (15th March 2019) - Tan, Kae Yi; Liew, Sin Teng; Tan, Qian Yi; Abdul-Rahman, Farah Nadhirah; Azmi, Nor Izzati; Sim, Si Mui; Tan, Nget Hong; Khomvilai, Sumana; Sitprija, Visith; Tan, Choo Hock
Abstract: Gel filtration chromatography and gel electrophoresis revealed minimal protein degradation in lyophilized antivenoms which were 2-year expired (Hemato Polyvalent, Neuro Polyvalent; Thailand) and 18-year expired (Hemato Bivalent, Neuro Bivalent; Taiwan). All expired antivenoms retained immunological binding activity, and were able to neutralize the hemotoxic or neurotoxic as well as lethal effects of the homologous snake venoms. The findings show that antivenoms under proper storage conditions may remain relatively stable beyond the indicated shelf life. Graphical abstract: Image 1 Highlights: Recent-expired (within 2 years) and aged (18 years) antivenoms were evaluated. Gel filtration chromatography and SDS-PAGE revealed minimal protein degradation. Both retained immunoreactivity toward the homologous venom proteins. Hemotoxicity, neurotoxicity and lethal effects of venoms were neutralized. With proper storage, they remained stable beyond the indicated shelf life.